An Exploration of Neighborhood Residents’ Cognition of and Participation in Low-Carbon Behaviors in Wuhan, China - Wenjun Peng; Xiaoming Wang; Lijun Guo (Advances in Civil Engineering)
This paper analyzed neighborhood residents’ cognition of and participation in low-carbon behaviors, basing on a questionnaire survey launched in a neighborhood in Wuhan, China. Results indicate that most respondents concerned the low-carbon impact on their daily lives and expected the government to make differences in low-carbon transition. Neighborhood residents’ participation in low-carbon behaviors was mainly reflected in three aspects: home energy conservation (HEC), efficient resource consumption (ERC), and recycling habits (RH), which were extracted from the five categories out of the 15 observed variables. Many interviewees had high level of participation in low-carbon behaviors that affect their economic interests. But these neighborhood residents rarely participated in public low-carbon behaviors such as planting trees or cooperative low-carbon behaviors. Therefore, these neighborhood residents’ participation in low-carbon behaviors was still on the initial stage. Specific proposals were put forward to promote urban low-carbonization further.